A study of upper gastrointestinal endoscopy in management of acute upper gastrointestinal bleed - Bansod, Atish N.; Shingade, Amarsingh; Mishra, Sarvagya (International Surgery Journal, 2021)
Background: Upper gastrointestinal bleeding (UGIB) is life threatening emergency that remains a common cause of hospitalization worldwide. In spite of tremendous advancement in management of upper gastrointestinal bleeding (UGIB) over past two decades, it carries considerable mortality, morbidity. The present study was undertaken to know the clinical profile, endoscopic profile, intervention, outcome and mortality of upper GI bleed. Methods: A total of 110 patients of UGIB were evaluated over a period of 30 months for etiology of UGIB like peptic ulcer, variceal bleeding, gastritis, Barrett’s esophagus and malignancy. Therapeutic Intervention (Band ligation, glue injection, clipping etc.) was done as required on case to case basis. Results: Hematemesis was the most common symptom with 62(56.36%) patients. 85(77.27%) patients were presented during first episode of their bleeding. Esophageal varices 50 (45.45%) was the most common diagnosis and the most common past history was alcohol intake 48 (43.63%). 55 (50%) patients required only medical (Pharmacological) management and 50 (44.54%) patients require endoscopic management. 102 (92.72%) were improved and subsequently discharged while 8 (7.27%) patients expired during the course of treatment. Conclusions: Endoscopic examination is an important modality in both diagnosis and managing UGIB and helps to reduce morbidity, mortality and also need for surgery of the disease significantly.